Evaluation of the cluster location decision on the performance of furniture manufacturing SMEs in Zimbabwe - Mapetere, Denver; Manhiwa, Thelma E R (IJECM Pub UK, 2021)
The study sort to establish the effects of cluster location decision on the performance of SME in the furniture manufacturing industry. Data for the study was collected from 69 SME owner/managers in the furniture manufacturing cluster industry located at Mkoba 6, Mtapa and DST complex in Gweru (the third largest city in Zimbabwe). The study deployed a structured questionnaire for data collection. A 100% response rate was obtained from the study and thus allowing study to make conclusions and generalize the results to the furniture manufacturing sector. The study found that SMEs performance is negatively affected by the cluster location decision as it leads to a high concentration of competitors in a single location, SMEs in clusters are restricted in their operations due to limited space allocated to them in the clusters, the majority of SMEs are not able to obtain sustainable benefits through knowledge spillovers in and around clusters. The study therefore recommends local government to involve SMEs in industrial park location and layout decisions so that location becomes are driver to operational success of small firms. It is imperative that town planning and zoning restriction take into consideration the internal heterogeneities of small firms when making agglomeration decisions rather than using the working definition of small firms. The study further recommends the allocation of operating space in designated areas to firms who are in the same line of business or who provide complementary services to the main line cluster so that all firms may benefit from agglomeration.